The between competition sprint profile of intercounty female gaelic football during training and match-play: An exploratory study - Eddie McGuinness; Mark Lyons; Kris Beattie; Aoife Lane; Clement Higginbotham; Robin Healy (PLoS ONE, 2026)
Female Gaelic football is an invasive field-based team sport but there are limited data on players’ sprint profiles. This study aimed to examine between-competition (league vs championship) differences during training and match-play, and to provide descriptive data by positional group. Fourteen players were monitored using 10-Hz GPS units (STATSports Apex) across 15 games and 34 training sessions. Key metrics included the number of accelerations and decelerations (≥ ± 3.0 m·s ⁻ ²), total sprints (≥ 20.0 km·h ⁻ ¹), sprint distances (<10 m, 10–20 m, 20–30 m, ≥ 30 m), average and total sprint duration and distance, peak speed, number of sprints at 80–90% and ≥90% of individual peak speed, and the highest percentage of peak speed achieved. In training, average sprint duration and distance, and sprints at 80–90% peak speed decreased from league to championship ( p < 0.05; ES 0.59–0.84), while peak speed increased ( p < 0.05; ES 0.61). In games, average sprint duration, number of sprints ≥30 m, and peak speed percentage achieved were greater in league games (p < 0.05; ES 0.36-0.73) compared to championship games. Despite the firmer surfaces of summer championship games, seasonal variations in training focus and in tactical and technical periodisation may explain the observed differences in running performance. These preliminary findings highlight the need for future research to examine how training periodisation, competition standard, and match demands interact to shape the running performance of female Gaelic football players.